A latent profile analysis of first-year university students’ academic expectations - Araújo, Alexandra M.; Assis Gomes, Cristiano Mauro; Almeida, Leandro S.; Núñez, Jose Carlos (Anales de Psicología / Annals of Psychology, 2018)
Academic expectations are an important variable in the explanation of adaptation and academic success in higher education. This paper uses latent profile analysis as a person-centered statistical approach to classify students into groups of similar types of expectations for higher education, at the beginning of the first year in university. Participants were 2,478 first-year Portuguese students. Based on the scores of seven dimensions of expectations, we identified six classes of students. Most students (84%) presented moderate levels of expectations, while 8% and 4%, respectively, reported very high and low expectations. One class represented a group of students (4%) with high expectations for the quality of education and for political engagement and citizenship and lower expectations for social interaction and attending to social pressures. Male and older students showed more positive expectations. Students from privileged family backgrounds are more likely to present higher expectations for political engagement and citizenship experiences, and lower expectations for social interaction and leisure and attending to social pressures. Keywords: latent profile analysis; person-centered; expectations; higher education; first-year students